Thermal hydraulics simulation of the RD-14M steam generator facility - Corzo, Santiago Francisco (2017)
A full three-dimensional Computational Fluid Dynamics simulation of the secondary circuit of a steam generator test facility was carried out. The multiphase flow was studied using the two-fluids Eulerian model. A constant boiling rate was assumed over the U-tubes walls and a blending model was applied for solving the interface momentum exchange. Steady-state conditions were simulated both by CFD and by a system code (Relap) with the aim to compare the recirculation flow rate, the flow through each one of the two riser legs and the five by-passes connecting the legs, the void distribution, the phase velocities and the pressure drop. The efficiencies of the separator and the dryer were also carefully studied. CFD and Relap results were in very good agreement with nominal data giving useful insights about the thermal hydraulics behavior of this kind of complex equipment and guidelines to carry on future CFD and system code simulations.